Images, Testimonies, and Wounds: Kamar and the Politics of the Gaze - Perrone, Nicolás (2023)
This paper delves into the poetics of Kamar, a theatrical group from La Rioja, Argentina. The analysis shows the aesthetic-political interests that are configured in their productions as part of a politics of the gaze. In this context, we analyze the play Nosotras en el espejo to understand the synthesis of the group's theatrical research in a particular piece. The key analysis of this play revolves around the image of the wound, materialized in a production whose origin is found in testimonies of gender violence. The use of the testimonial theatrical device allows the exploration of a game of mirrors that alters the spectator's passive gaze and transmutes it into an emancipated and active gaze, conjugated in the order of affections and performative action.